Health-related quality of life after thrombectomy in young-onset versus older stroke patients: a multicenter analysis. (7th December 2021) - Deb-Chatterji, Milani; Pinho, João; Flottmann, Fabian; Meyer, Lukas; Broocks, Gabriel; Brekenfeld, Caspar; Reich, Arno; Fiehler, Jens; Gerloff, Christian; Thomalla, Goetz
Abstract : Background: Information is lacking on self-reported health-related quality of life (HRQoL) as a complementary outcome measure in addition to the modified Rankin scale (mRS) in young patients with ischemic stroke after endovascular thrombectomy (EVT) compared with older patients. Methods: Data on consecutive patients with stroke who underwent thrombectomy (June 2015–2019) from a multicenter prospective registry (German Stroke Registry) were analyzed. HRQoL was measured by the European QoL-5 dimension questionnaire utility index (EQ-5D-I; higher values indicate better HRQoL) 3 months after stroke in patients aged ≤55 and >55 years. Multivariate regression analyses identified predictors of better HRQoL. Results: Of 4561 included patients, 526 (11.5%) were ≤55 years old. Young-onset patients had a better outcome assessed by mRS (mRS 0–2: 64.3% vs 31.8%, p<0.001) and EQ-5D-I (mean 0.639 vs 0.342, p<0.001). Young survivors after EVT had fewer complaints in the EQ-5D domains mobility (p<0.001), self-care (p<0.001), usual activities (p<0.001) and pain/discomfort (p=0.008), whereas no difference was observed in anxiety/depression (p=0.819). Adjusted regression analysis for 90-day mRS showed no difference in HRQoL between the two subgroups of patients. Lower age, National Institutes of Health Stroke Scale score and pre-stroke mRS, a higher Alberta Stroke Program Early CT Score, concomitant intravenous thrombolysis therapy and successful recanalization were associated with better HRQoL in both patient subgroups. Conclusions: Young-onset stroke patients have a better HRQoL after EVT than older patients. Their higher HRQoL is mainly explained by less physical disability assessed by mRS. Depressive symptoms should be actively assessed and targeted in rehabilitation therapies of young-onset stroke patients to improve quality of life after stroke.